Me and the Robbersons - Kolu, Siri 1972- (Me and the Robbersons, 2021)
Maisie is convinced her summer holiday is going to be as boring as ever - until a bungled raid on her family's car sees her snatched by the Robbersons, a bunch of bandits with an insatiable appetite for sweets! Soon Maisie realises that life on the open road with the Robbersons is the adventure she's always longed for. They've even started to see her as one of the gang! So when she discovers that the police and her parents are hot on their trail, Maisie decides she isn't quite ready to be rescued ...